Renal Allograft Rejection: Role of Tc99m-DTPA Renal Scan (Medical Forum Monthly, 2024)
Objective: Tc99m- diethylene triamine pentaacitic acid (DTPA) renal renography has been used to evaluate renal transplant function with variable results. In this study we compared the results of renal scan with biopsies of renal allograft to evaluate the ability of renography to differentiate acute rejection from other causes of allograft dysfunction including acute tubular necrosis (ATN) and medication toxicity.Study Design: Observational / cross sectional study.Place and Duration of Study: This study was carried out in the Hope Kidney Clinic, Texas, USA from January 1, 2011 to December 31, 2012Materials and Methods: All renal transplant patients at Hope Kidney Clinic, Laredo, Texas, USA who had Tc99m-DTPA renal scan for elevated serum creatinine and subsequent biopsy within 48 hours were included. A total of eighteen patients underwent allograft biopsy. We tested the hypothesis that decreased flow and function would predict acute rejection and in other etiologies such as ATN normal flow with or without impaired function would be seen.Results: Four of 9 patients (44%) with impaired flow and function on renography had acute rejection, three of which has vascular component. Four of 9 patients (44%) with normal flow with or without normal function had rejection, none of which has a vascular component.Conclusion: Based on these findings, it was concluded that Tc99m-DTPA renography is neither sensitive nor specific for the detection of acute allograft rejection butTc99m-DTPA renography may be more sensitive for detecting rejections with vascular component as all of those in this study demonstrated.